Distribution, Population, and Habitat of Siamang (Symphalangus syndactylus) in Bulu Mario, South Tapanuli - Safira Arda Meylia; Abdul Haris Mustari (Jurnal Penelitian Hutan dan Konservasi Alam, 2022)
The population of siamang in the forest around Bulu Mario Village needs attention even though it is outside the conservation area. Therefore, this study was conducted using survey methods, vegetation analysis, and concentration count. Based on the data, siamang was distributed at an elevation of 683 - 1123 m asl in forest and mixed plantations with a dominant slope of 70.02%. Furthermore, the population was 44 individuals from 15 groups with a density of 2.88 individuals/km2, and the ratio of adult males to females was 14:12. The age classes of adults and juvenile-1 dominated the age structure pyramid; hence, the population's sustainability is considered good enough. Also, the low population density of the primate is due to habitat fragmentation in several locations. The siamang uses the entire canopy space and is associated with various other primates. Both hayu ndolok (Syzygium sp.) and rubber (Hevea brasiliensis) are the tree species with the highest abundance in the forest and mixed plantations. The siamang eats more of the fruit of 51 plant species dominated by the Euphorbiaceae family and tree habitus. Therefore, the development of animal corridors is needed to reduce the impact of habitat fragmentation.